PROFILE OF SELF-CONFIDENCE VIEWED FROM FAMILY SOCIAL STATUS IN STATE JUNIOR HIGH SCHOOL STUDENTS IN PANGANDARAN DISTRICT - Lestari, Tri; Yatim, Ab Aziz Mihd; Pernantah, Piki Setri; Prasetiawan, Hardi (Universitas Pendidikan Indonesia, 2023)
Self-confidence is a key factor in forming identity and adolescent well-being. This can affect a adolescent life, including interpersonal relationships, academic achievement, and future success. Family social status is the social position held by a family in a society, which reflects the level of prestige, access to resources, and roles recognized by society. In social life, there are at least three kinds of positions, namely: (1) Ascribe status, (2) Achieved Status, (3) Assigned Status. In this study, it will reveal how self-confidence (self-confidence) of students in terms of family social status. The purpose of this article is to describe the self-confidence profile of students in terms of family background and parenting style. The research method used in this research is a quantitative approach with a survey research design, a type of cross-sectional survey. The instrument used in this study was the Self-confidence inventory which was adapted from Gael Lindenfield's theory. Participants who were respondents in this study were junior high school students from public junior high schools in Pangandaran Regency, which consisted of three schools, namely: (1) Pangandaran 1 Public Middle School; (2) Pangandaran 2 Public Middle School; (3) Pangandaran 3 Public Middle School The number of respondents involved in this study was 150 people. The sample selection uses a probability sampling technique with total or saturated samples. The results of this study generally show that the self-confidence of junior high school youth in Pangandaran Regency tends to be in the medium category. Moreover, students with family social status who have a role in society tend to have high and moderate self-confidence. As for suggestions for future researchers who will conduct similar research, to conduct research by adopting a mixed method approach between quantitative and qualitative to obtain a more comprehensive understanding.